PENGEMBANGAN SOFSKILL TEKNIK PENGELASAN BAGI GENERASI MUDA USIA PRODUKTIF UNTUK MEMBUAT HOME INDUSTRI MELALUI PELATIHAN PROSES PENGELASAN - Yeni Suhartini; Anizar Indriani; Muhammad Syaiful (DHARMA RAFLESIA, 2017)
Welding processing is the process to make some part of metal become a unit by using heat. Some application of welding process can be seen at the fence, truss, door, gate and etc.The fence, trellis windows and doors and a gate are made from iroin highly prevalenttoday. The Iron fence, trellis for windows and doors as well as the gate is made anddesigned to make home become beautiful. The fencing, railing, and gating are usingwelding machines to connect and decorate the desired shapes. Expertise in designing andwelding of products are very important to meet the requirement of customers. As seen fromthe shape and style of fences and trellises shows the state of community identity in thearea. Expertise to design and design as well as the use of welding machines can beobtained by the public through formal education in Vocational High School of Engineeringand informal (BLK). In addition to the society through education can not study theprocesses undertaken to make tools or products such as fences, trellises and the gate. It isvery harmful for people who do not have a chance to get a formal education or informal.Through community service, which is part of the Tri Dharma College conducted thetransfer of knowledge to the people who did not get a formal or informal education to practice making these objects with the welding process. With this training adds insight andknowledge society. From the results of this training is seen that people who can not followthe formal and informal education have a high desire to attend this training. This is toimprove the economy and living standards by utilizing the welding knowledge to createnew jobs or working with existing workshops.Keywords: Welding Technique, Productive Age, Training